Kingdom of the Netherlands-Netherlands : 2006 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2006)
The Netherlands showed economic recovery, supported by strong polices, public finances, and structural reforms. Executive Directors commended the strong fiscal framework and agreed that it meets the good practice standards according to the reports on the observance of standards and codes. They commended the sound financial system and welcomed the new Financial Supervision Act. They emphasized the need for fiscal consolidation for securing fiscal sustainability. Directors appreciated the authorities' responsiveness to the recommendations of the Financial System Stability Assessment.